Tin dioxide based thin film gas sensor of hydrogen - Dmitriev, Serghei (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2005)
Results of investigation of the SnO2 thin films sensitivity towards to hydrogen are presented. Films were deposited by chemical spray pyrolysis method on ceramic substrate. Study of electrical characteristics of obtained layers has shown that the latter possess resistance on the level 105 -106 Ohm at the working temperatures 200-250 o C. Gas sensitivity S of deposited thin films amounted 95-100 relative units to 0.1 vol.% of hydrogen in air. Optimization of gas sensitive properties of tin dioxide films through bulk and surface doping with Pd and Cu has allowed increasing of hydrogen sensitivity up to 103 rel. units. Simultaneously, the considerable shift of the working temperatures of such sensor to the low temperature value (150o C) was achieved.